Effect of nutrient management practices on soil fertility and productivity of dual purpose Oat (Avena sativa L.) - DADHICH, S.K.; VERMA, R.; KUMAWAT, C.; AGARWAL, R.K.; SHILPKAR, P. (Journal of Soil and Water Conservation, 2025)
A field experiment was conducted at Agronomy farm, S.K.N. College of Agriculture, Jobner, Rajasthan. The trial was initiated to find out the effect of nutrient management practices on soil properties and productivity of dual purpose oat from rabi, 2020-21 to rabi, 2022-23 for continuous 3 years. The treatments included T1-Control (No nutrients), T2-N: P2O5: K2O -100:40:40 kg/ha, T3-75% of RDF + Vermicompost @ 2t/ha, T4-T3 + PSB @ 1.5 kg/ha(in Soil), T5-T4 + Seed treatment with Azotobacter @ 10 g/kg seed, T6-T5 + ZnSO4 @ 20 kg/ha (soil application as basal), T7-T5 + ZnSO4 @ 15 kg/ha (soil application as basal), at just before flowering, T8- T6 + Foliar spray of ZnSO4 @ 0.5% at just before flowering and T9-T7 + Foliar spray of ZnSO4 (0.5%) at just before flowering. Treatments were replicated thrice in Randomized Block Design. The results revealed that among the nine treatments, T8- 75% of RDF+ Vermicompost @ 2t/ha + PSB application to soil @ 1.5 kg/ha + seed treatment with Azotobacter + ZnSO4 @ 20 kg/ha (soil application as basal) + foliar spray of ZnSO4 (0.5%) just before flowering resulted in significantly highest plant height (88.0, 88.8 and 89.7 cm), green fodder yield (282, 275.5 and 279.4 q/ha), seed yield (21.67, 24.11 and 26.19 q/ha), straw yield (72.67, 84.1 and 91.36 q/ha) and crude protein content in seed (12.18, 12.10 and 12.30 %), respectively during all the three years i.e. 2020-23. However, the effect of treatment T8 remained statistically at par with treatment T6, T7 and T9. Further, the treatment T8, resulted in build up of available N (164.86 kg/ha), P2O5 (32.15kg/ha), K2O (285.36 kg/ha) and DTPA-Zn (0.819 mg/kg) in soil at harvest of oat after 3rd year.